A perspective on complex networks in the stock market - Park, Jihun; Cho, Chang Hee; Lee, Jae Woo (Frontiers in Physics, 2022)
A stock market is a complex system consisting of many interacting agents. We consider recent progress with complex networks constructed from cross-correlation of financial time series in the stock market. We review some methods and discuss the challenges in generating such complex networks that have a reasonable threshold.